2007
DOI: 10.1073/pnas.0610348104
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the Escherichia coli AmtB–GlnK complex reveals how GlnK regulates the ammonia channel

Abstract: Amt proteins are ubiquitous channels for the conduction of ammonia in archaea, eubacteria, fungi, and plants. In Escherichia coli, previous studies have indicated that binding of the P II signal transduction protein GlnK to the ammonia channel AmtB regulates the channel thereby controlling ammonium influx in response to the intracellular nitrogen status. Here, we describe the crystal structure of the complex between AmtB and GlnK at a resolution of 2.5 Å. This structure of P II in a complex with one of its tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
257
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(265 citation statements)
references
References 38 publications
5
257
0
3
Order By: Relevance
“…By similarity with M. jannaschii GlnK1, MgATP, and ADP binding to P II should trigger, respectively, the compact and highly extended T-loop conformations (13,15), explaining the dissociation of the P II -NAGK complex by ADP but not by MgATP (6). These MgATP and ADP effects on the T-loop fit the proposed P II role in energy signaling in cyanobacteria (10).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…By similarity with M. jannaschii GlnK1, MgATP, and ADP binding to P II should trigger, respectively, the compact and highly extended T-loop conformations (13,15), explaining the dissociation of the P II -NAGK complex by ADP but not by MgATP (6). These MgATP and ADP effects on the T-loop fit the proposed P II role in energy signaling in cyanobacteria (10).…”
Section: Discussionmentioning
confidence: 61%
“…The indirect effects of P II on NAGK functionality contrast with the direct role of GlnK in blocking the ammonia channel AmtB (14,15). In the latter case, the tip of the ADP-binding and more extended T-loop, including nonuridylylated Y51, blocks the cytoplasmic opening of the channel.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Two partially stacked phenyl rings, F107 and F215 in AmtB, are seen at the periplasmic pore entrance in all Amt structures (4,5,24,25) and appear to severely constrict the substrate pathway (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…A more recent experiment [36] found that ammonium was not toxic at realistic physiological concentrations. However, ammonium cannot diffuse through the cell membrane and E. coli cells are known to deactivate the membrane ammonium transporter AmtB when exposed to a high-ammonium environment [3739]. This may explain why the experiment in [36] did not see a detrimental effect of ammonium on initial growth rates, while other experiments have seen an effect of ammonium on the viability of E. coli after long exposures [28, 29].…”
Section: Discussionmentioning
confidence: 99%